2018
DOI: 10.1590/s1517-707620180004.0569
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube reinforced polymer as a bonded repair for Al 2024-T3 fatigue crack growth

Abstract: The influence on multi walled carbon nanotubes (MWCNT, or simply CNT) as a reinforcement material in an epoxy resin in order to decrease the fatigue crack propagation rate in the 2024 T3 aeronautical Al alloy was studied. CT samples were pre-cracked in a resonant fatigue machine until a 4 mm pre-crack length. Four groups of samples were considered: a non-repaired reference group, two groups repaired with epoxy resin reinforced with two CNT proportions (0.5 and 1 vol %) and a group repaired by the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some factors, such as functionalization, purity, size, length, diameter, poor or no dispersion in water, surface chemistry, and no treatment for disposal, enhance the toxicity of CNTs in nature [5]. Because of the large production and wide application of these nanocomposites in various sectors of society, assessing the impact of CNTs on the environment is essential [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some factors, such as functionalization, purity, size, length, diameter, poor or no dispersion in water, surface chemistry, and no treatment for disposal, enhance the toxicity of CNTs in nature [5]. Because of the large production and wide application of these nanocomposites in various sectors of society, assessing the impact of CNTs on the environment is essential [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This work further revealed that CFRP patch is a feasible choice for repairing damaged metal structures. Monsalve et al [17] selected CNTs as a reinforcement in the epoxy resin to decrease the fatigue crack propagation rate in the 2024 T3 Al alloy. The results showed that a small amount of CNTs is helpful to extend the fatigue crack propagation life of Al alloy structures.…”
Section: Introductionmentioning
confidence: 99%
“…That work foundd that CFRP patching is a feasible choice for repairing damaged metal structures. Monsalve et al [ 18 ] selected CNTs as a reinforcement in epoxy resin to decrease the fatigue crack propagation rate in a 2024 T3 Al alloy. The results showed that a small amount of CNTs is helpful in extending the life of Al alloy structures with fatigue crack propagation.…”
Section: Introductionmentioning
confidence: 99%